Analisis Persepsi Pasien Tentang Mutu Pelayanan Rawat Jalan Di Puskesmas Pakjo Kota Palembang Tahun 2017 - Ashfari, Ryan Ashfari (IKEMAS: Jurnal Ilmu Kesehatan Masyarakat, 2018)
Quality of serviceis an indicator for th eperformance of health careproviders such as health center. Health centerwill be more advancedif the performance canbe maintained. Toretain customers, tobe able tomeasure the health center servicewhich includes the five dimensions ofservice quality, namely: reliability, responsiveness, assurance, empathy, and tangible. The purpose  of this study was to determine the patient's perception of service quality outpatient at Pakjo Health Center Palembang from 5 a spectsof service quality. This type of researchis qualitative research with descriptive analysis taken by depth intervievs and observation . The main in formant was six out patients consisting of two general patients, two ASKES patients and two BPJS patients, while theinformant triangulation were head of Pakjo Health Center and head of out patient department. The results showed that theservice quality Out patient at Pakjo Health Centeral ready meet sall five aspect of quality service include reliability, responsiveness, assurance, empathy, and tangible. The most streng then ed istangible, from the results of depth interviews with patient and also triangulation with the head ofthe health center that issince the new building of health center, the patient increased and more comfortable, As well as there searchers look directly at the time of observation.And for aspects ofreliability, assurance, and empathy all patients had the same percepti on that Out patient at Pakjo Health Center in good and no complaints. Results showed for responsiveness aspect, they have many complaints, that the patient complained ofqueues Pharmacies, and from interviews with head out patient department alsoal ready known to the complaint.As for the other complaintsrelated to the lack of drugs in the period of BPJS validity, Head ofPakjo Health Center currently do not have the aut hority to take the solution, can only convey there levant parties. From the analysis results it was concluded that quality service outpatient at Pakjo the health centeris optimal because each of ficeral ready function well according tuposiandi sperceived by the patients who come in, and there should bean in crease in future, so no complaints from patients again.